Physiopathological Role of the Vesicular Nucleotide Transporter (VNUT) in the Central Nervous System: Relevance of the Vesicular Nucleotide Release as a Potential Therapeutic Target - Miras-Portugal, María T.; Menéndez-Méndez, Aida; Gómez-Villafuertes, Rosa; Ortega, Felipe; Delicado, Esmerilda G.; Pérez-Sen, Raquel; Gualix, Javier (Frontiers in Cellular Neuroscience, 2019)
Vesicular storage of neurotransmitters, which allows their subsequent exocytotic release, is essential for chemical transmission in the central nervous system. Neurotransmitter uptake into secretory vesicles is carried out by vesicular transporters, which use the electrochemical proton gradient generated by a vacuolar H+-ATPase to drive neurotransmitter vesicular accumulation. ATP and other nucleotides are relevant extracellular signaling molecules that participate in a variety of biological processes. Although the active transport of nucleotides into secretory vesicles has been characterized from the pharmacological and biochemical point of view, the protein responsible for such vesicular accumulation remained unidentified for some time. In 2008, the human SLC17A9 gene, the last identified member of the SLC17 transporters, was found to encode the vesicular nucleotide transporter (VNUT). VNUT is expressed in various ATP-secreting cells and is able to transport a wide variety of nucleotides in a vesicular membrane potential-dependent manner. VNUT knockout mice lack vesicular storage and release of ATP, resulting in blockage of the purinergic transmission. This review summarizes the current studies on VNUT and analyzes the physiological relevance of the vesicular nucleotide transport in the central nervous system. The possible role of VNUT in the development of some pathological processes, such as chronic neuropathic pain or glaucoma is also discussed. The putative involvement of VNUT in these pathologies raises the possibility of the use of VNUT inhibitors for therapeutic purposes.